TEMPORAL ANALYSIS OF THE PRODUCTIVITY OF THE DOMINANT CAPTURE FISHERIES COMMODITY (CASE IN THE SOUTHERN WATERS OF THE SPECIAL REGION OF YOGYAKARTA – WPP NRI 573) - Prakoso, Bagas; Suyasa, I Nyoman; Rahayu, Siti Mira (Politeknik Kelautan dan Perikanan Dumai, 2025)
Climate variations can affect sea surface temperature (SST), feed distribution, and fish habitat. Temporal analysis of SPL and chlorophyll-a can help identify the impact of climate change on capture fisheries productivity. This study aims to analyze the relationship between chlorophyll-a and sea surface temperature (SST) on the productivity of dominant capture fishery commodities in the southern waters of the Special Region of Yogyakarta I-FMA 573. Fisheries productivity data on five dominant fish species at the research site (yellowfin tuna (Thunnus albacares), skipjack tuna (Katsuwonus pelamis), savalai hairtail (Trichiurus savala), Indian scad (Decapterus russelli), and common dolphinfish (Coryphaena hippurus)) in 2014-2023 were collected from PPP Sadeng. Chlorophyll-a and SST data for 2014-2023 were obtained from Aqua Modis multisensory satellite imagery. The data was classified based on the four seasons in Indonesia allowing analysis of seasonal changes affecting fisheries productivity. Skipjack tuna has the highest productivity, with an average of 410,803 kg/trip, while common dolphinfish has the lowest productivity, with an average of 29,521 kg/trip. Based on the results of multiple linear regression, chlorophyll-a and SST had a significant effect on the productivity of yellowfin tuna, skipjack tuna, Indian scad, and common dolphinfish, so that chlorophyll-a and SST may indicate the presence of these fish populations. Meanwhile, savalai hairtail are not significantly affected by chlorophyll-a and SST, because many environmental factors affect including monsoon winds, currents, and rainfall.